Training and minimum wages: First evidence from the introduction of the minimum wage in Germany - Lutz Bellmann; Mario Bossler; Hans-Dieter Gerner; Olaf Hübler (IZA Journal of Labor Economics, 2017)
We analyze the short-run impact of the introduction of the new statutory minimum wage in Germany on further training at the workplace level. Applying difference-in-difference methods to data from the IAB Establishment Panel, we do not find a reduction in the training incidence but a slight reduction in the intensity of training at treated establishments. Effect heterogeneities reveal that the negative impact is mostly driven by employer-financed training. On the worker level, we observe a reduction of training for medium- and high-skilled employees but no significant effects on the training of low-skilled employees.
Keywords: C23; I26; J24; J38; 330; Minimum wage; Training; Difference-in-differences